Information Communication Technology Access and Use towards Energy Consumption in Selected Sub Saharan Africa - Ihayere, Oseghale Baryl; Alege, Philip Olasupo; Gershon, Obindah; Ejemeyovwi, Jeremiah Ogaga; Daramola, Praise (International Journal of Energy Economics and Policy, 2020)
Major new opportunities abound from energy integration among regions in Africa with the sole aim of reducing transaction costs and with the role of Information Communication Technology (ICT), it would take energy from where it is easily affordable to places where it is needed. Given the hullabaloo over the net energy-saving impact of ICT, this study takes on a new perspective, that is, employing household energy consumption, to ascertain the use of ICT by household in accessing energy. The study reconnoiters the degree to which Energy integration among the five regional power pools in Africa can achieve ending energy poverty among regional adherents by means of three measures of energy sustainability, explicitly: energy security, energy equity and environmental sustainability. The study utilizes the Pooled Ordinary Least Squares technique on data from the SSA economies over the period 2000-2019. The study expects the results to help in suggesting the need for the acceleration of ICT development in Africa (Sub-Saharan) nations, given the universal communal mission of sustainable energy consumption. Keywords: Technology and Distribution, Common Knowledge, Aggregate Energy Consumption, Sustainable Development, Green Technology, ICT-based JEL Classifications: O330, D8, Q430, QO10, Q4, Q550, O300, D13 DOI: https://doi.org/10.32479/ijeep.9990